A structured dataset of the federalist society’s public engagements [version 2; peer review: 2 approved] - Chad M. Topaz (F1000Research)
Background The Federalist Society, a leading conservative legal organization, has played a significant role in shaping the American judiciary for decades. Despite its influence, comprehensive empirical data on the organization remains scarce. We address this gap by systematically documenting 20,205 public events hosted by the Society from 1984 to 2024, with substantive coverage from 2007 onward. Methods Following ethical best practices in data collection and ownership, we gathered event metadata—including titles, dates, locations, sponsors, topics, and speakers—via web scraping from the Federalist Society’s archives. The dataset is structured to facilitate analysis of event trends, co-speaking networks, and thematic shifts over time. To ensure data integrity, we performed validation, deduplication, and cleaning, resulting in a well-structured, high-quality dataset. Conclusions This dataset provides an empirical foundation for examining the Federalist Society’s role in legal discourse. It is a resource for scholars in law, political science, sociology, gender studies, network science, and computational social science, enabling investigations into key themes of discussion, event participation patterns, demographic diversity, professional backgrounds, and more. Researchers can use it to study institutional influence, legal networks, and the evolution of conservative legal thought.